Dog bites: how big a problem?. Issue 1 (March 1996) - Sacks, J. J.; Kresnow, M.; Houston, B.
Abstract : OBJECTIVE: To estimate the magnitude of the dog bite problem in the US. METHODS: Data on dog bites were gathered as part of a 1994 national telephone survey of 5, 238 randomly dialed households. Data were weighted to provide national estimates. RESULTS: The weighted total number of dog bites was 4, 494, 083 (estimated incidence = 18/1, 000 population); of these, 756, 701 persons sustained bites necessitating medical attention (incidence rate = 3/1, 000). Children had 3.2 times higher medically attended bite rates than adults (6.4/1, 000 children v 2/1, 000 adults). CONCLUSIONS: More attention and research needs to be devoted to the prevention of dog bites. Potential prevention strategies include: educational programs on canine behavior, especially directed at children; laws for regulating dangerous or vicious dogs; enhanced animal control programs; and educational programs regarding responsible dog ownership and training. Unfortunately, the relative or absolute effectiveness of any of these strategies has not been assessed. Continuing surveillance for dog bites will be needed if we are to better understand how to reduce the incidence of dog bites and evaluate prevention efforts.